Isla de calor urbano superficial y demanda energética: visualización de los flujos climáticos urbanos - Jorge Rodríguez-Álvarez (Pós: Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2016)
The surface urban heat island (SUHI) effect can be defined as the relative warmth of urban surfaces compared with its surroundings due to the difference in their respective cooling rates. Classic studies have demonstrated that urban warming is a regional and occasional phenomenon whose occurrence depends on weather conditions and characteristics of the urban fabric. Satellite imagery and GIS are combined in this paper to unveil patterns in thermal variations across cities and relate air temperature to density or land cover. Six European regions were selected: Madrid (40ºN, 3ºE), Cologne (50ºN, 6ºE), Barcelona (41ºN,2ºE) London (51ºN,0.5ºW), Brussels(50ºN,4ºE) and Berlin(52ºN,13ºE). Images with information on surface temperature were obtained from Modis Satellite database. Over 120 files were scrutinized to select 6 winter and summer days and nights. From these, six summer nights are presented as they offer the clearest land surface temperature distribution. The spatial correlation between air temperature, density and land cover was analysed in GIS and plotted as citywide cross sections. The strongest correspondence was found between density and land cover. Finally, the influence of UHI in the energy demand of domestic buildings in London and Barcelona was investigated. This analysis showed the greater relative impact of this phenomenon in warmer regions.